Effects of betulinic acid on synovial inflammation in rats with collagen-induced arthritis. (July 2020) - Kun-Liu; Wang, Jian-Ying; Zhang, Lei; Pan, Ying-Yi; Chen, Xiao-Yun; Yuan, Ying
Betulinic acid (BA) inhibits the migration, invasion, and cytoskeletal reorganization of fibroblast-like synoviocytes (RA-FLS) in patients with rheumatoid arthritis. Here, to further explore the mechanism of action of BA in collagen-induced arthritis (CIA) rats, we investigated the pharmacodynamic effects of BA on synovial inflammation in a rat model of type II CIA. After inducing hind paw swelling, the rats were divided into four groups: healthy controls (normal), and rats that underwent CIA and received methotrexate treatment (MTX), BA treatment (BA), or no treatment (CIA). Body weight and hind paw swelling were determined regularly, and arthritis scores were calculated weekly. On day 35, rats were sacrificed and their hind ankle joints sectioned and stained with hematoxylin and eosin for histopathological evaluation. BA significantly reduced CIA-induced hind paw swelling, synovial tissue proliferation, cartilage destruction, and vasospasm. BA treatment also decreased serum interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha (TNF-α) levels in rats with CIA. The CCK-8 assay was used to detect the proliferation of isolated vimentin + CD68 − RA-FLS; RA-FLS were stimulated with TNF-α in vitro. BA significantly inhibited TNF-α-stimulated RA-FLS proliferation, as well as IL-1β and IL-6 secretion. BA also downregulated the transcription of vascular endothelial growth factor (VEGF) and transforming growth factor β (TGF-β) and decreased the expression of the NF-кB pathway proteins (NF-kB-P65, IkBα, and IKKα/β) in the TNF-α-stimulated RA-FLS. These results indicate that BA alleviated the symptoms of CIA by inhibiting synoviocyte proliferation, modifying TNF-α- and NF-кB-related inflammatory pathways, and downregulating inflammatory mediators and growth factors including IL-1β, IL-6, VEGF, and TGF-β.